Proteínas quinases envolvidas na regulação do estresse em Trypanosoma - Jesus, Teresa Cristina Leandro de [UNIFESP] (2010)
Protozoa of the genus Trypanosoma have a complex life cycle alternating between vertebrate and invertebrate hosts. The adaptation to different environmental conditions requires rapid changes in gene expression to fill up the morphological and metabolic requirements for survival. Very little is known about the mechanisms that control these changes and the signaling pathways involved. As in these organisms the control of gene expression occurs at post-transcriptional level, in this work we decided to investigate the function of protein kinases involved in the control of protein synthesis and growth of these parasites. In several eukaryotes TOR (target of rapamycin) protein kinases are involved in protein synthesis control and cell growth in response of the availability of nutrients or growth factors. By searching T. brucei genomic database we found four candidates for TOR (TbTOR1, TbTOR2, TbTOR-like1 and TbTOR-like 2). Two TOR complexes were previously described in T. brucei (TbTORC1 and TbTORC2). In the first chapter of this thesis we study: TbTOR-like 1 and compared it with TbTOR2. TbTOR-like 1 is not present in any of the TORC complexes and has a PDZ domain not found in any of other TORs of T brucei, or other eukaryotes. It is located cytosolic granules that migrate to the cell periphery after hyperosmotic stress. Depletion TbTOR-like 1 causes a progressive inhibition of cell growth, generating enlarged cells that accumulate in S/G2 phase of the cell cycle. These cells also show increased number of acidocalcisomes and augmented levels of polyphosphate and pyrophosphate. These data indicate that TbTOR-like seems to be involved in controlling cell growth and biogenesis of acidocalcisomes responding to osmotic changes in the medium. In the second chapter of the thesis we studied protein kinases involved in protein synthesis control through the phosphorylation of the  subunit of the eukaryotic translation initiation factor 2 (eIF2α).These kinases are activated by different types of stress. T. brucei encodes three potential eIF2α protein kinases (TbeIF2K1, K2 and K3). We studied more specifically the K2. We showed that it is a transmembrane glycoprotein located in the region of the flagellar pocket in both forms of T. brucei, and in the endosomal compartments of Trypanosoma cruzi. These endosomal compartments are known as reservosomes and they are formed only in the parasite’s stage that li ves in the digestive tract lumen of the insect vector. This fact suggests that in both parasites this protein kinase may be acting as a sensor in the transport of nutrients and proteins. In conclusion we revealed the existence of at least two mechanisms by which trypanosomes perceive and resist to environmental changes during their life cycle.